The Application of Intuitionistic Fuzzy Set-TOPSIS Model on the Level Assessment of the Surrounding Rocks - Xin-bao Gu; Ying Ma; Qi-hong Wu; Yang-bing Liu (Shock and Vibration)
The level assessment of surrounding rocks in underground tunnels has essential significance for the stability of surrounding rocks. Its review is affected by many factors. The intuitionistic fuzzy set-TOPSIS model is first introduced to estimate the quality of surrounding rocks accurately. Secondly, the decisive matrix of the intuitionistic fuzzy sets is established. Then, the weighed decisive matrix is obtained. Finally, the degree of membership at different levels regarding the surrounding rock quality is determined. The quality level corresponding to the maximum degree of membership is the final assessment level. The conclusions are drawn that estimating the quality level of surrounding rocks using the method is feasible compared to the actual investigations and other methods. This method can reflect the quality level of surrounding rocks accurately, providing a new route for the quality assessment of surrounding rocks in the future.